2022
DOI: 10.3892/ijmm.2022.5185
|View full text |Cite
|
Sign up to set email alerts
|

ZNF667 facilitates angiogenesis after myocardial ischemia through transcriptional regulation of VASH1 and Wnt signaling pathway

Abstract: Zinc finger protein 667 (ZNF667, also referred as Mipu1), a widely expressed KRAB/c 2 H 2 -type zinc finger transcription factor, can protect against hypoxic-ischemic myocardial injury. Pro-angiogenesis is regarded as a promising strategy for the treatment of acute myocardial infarction (AMI). However, whether ZNF667 is involved in the angiogenesis following AMI remains to be elucidated. The present study reported that the expression of ZNF667 in cd31-positive endothelial cells (Ecs) was upregulated in the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…This aligns with our ndings that USP49 reduces the level of troponin in the blood (genetically predicted expression of USP49 had a negative impact on troponin levels). FRAT1 is involved in Wnt signaling pathway which is regulated after myocardial ischemia to facilitate angiogenesis by ZNF667 20 . ZNF667 shows inhibitory effects on canonical Wnt pathway-related genes including FRAT1 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with our ndings that USP49 reduces the level of troponin in the blood (genetically predicted expression of USP49 had a negative impact on troponin levels). FRAT1 is involved in Wnt signaling pathway which is regulated after myocardial ischemia to facilitate angiogenesis by ZNF667 20 . ZNF667 shows inhibitory effects on canonical Wnt pathway-related genes including FRAT1 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the suggestion that KZFPs act to facilitate the domestication of the regulatory potential of TEs, which had been proposed long ago to be key to the establishment and evolution of gene regulatory networks (Trono 2015;Britten and Davidson 1969). In line with this hypothesis, individual human KZFPs have been found to be implicated in a variety of biological processes, including embryonic genome activation, gastrulation, gametogenesis, imprinting, placentation, brain development, adipogenesis and angiogenesis (Chen et al 2019;Playfoot et al 2021;Pontis et al 2019Pontis et al , 2022Hayashi and Matsui 2006;Takahashi et al 2019;Quenneville et al 2011;Wagner et al 2000;Zeng et al 2012;Yang et al 2017a;Wang et al 2022;Iouranova et al 2022;Li et al 2008). An important step towards defining the roles of all human KZFPs lies in a more complete characterization of their genomic targets.…”
Section: Introductionmentioning
confidence: 93%
“…VASH1 is involved in tumorigenesis, atherosclerosis, age-dependent macular degeneration, and diabetic retinopathy ( 40 , 41 ). Wang et al ( 42 ) reported that the expression of VASH1 increased rapidly in the ischemic myocardium following AMI. However, the role of VASH1 in AF has not been explored.…”
Section: Discussionmentioning
confidence: 99%